The Impact of Victimization, Mental Health Problems, and Disabilities on Juvenile Justice Processing: does Gender Matter? - Chappell, Allison T. (Crime & delinquency, 2021)
Victimization, mental health problems, and disabilities are associated with an increased likelihood of delinquent behavior, and girls in the juvenile justice system report higher rates of past trauma and victimization, sexual abuse, and mental health issues than boys. However, the influence of these problems on juvenile justice processing remains understudied. This study investigated the impact of victimization, mental health problems, disabilities, and comorbidity on intake and adjudication decisions across gender. Data on 74,636 intake cases were obtained from the centralized database of the juvenile justice office in a mid-Atlantic state (FY 2011-2015). Findings suggest that mental health problems, victimization, and disabilities are associated with increased punitiveness at intake but few consistent gender differences emerged. Implications for policy and practice are discussed.